Strolling in Tel Aviv: setting up and breaking down boundaries in S. Yizhar's preliminaries (Mikdamot) - Tzur, Dvir (AJS review, 2017)
The article discusses the image of Tel Aviv, the first Hebrew city, as it is described in the novel Preliminaries by S. Yizhar (Yizhar Smilansky), one of Israel's best-known authors. In this novel, which engages with the question of home and borders, borders function as a double-edged sword: on the one hand, they define home and create a circumscribed place for the protagonist and his family. On the other hand, the novel dwells on the urge to cross borders and shatter the distinction between home and the world. In this regard, Tel Aviv is sometimes described as a pleasant, “normal” city, yet at other times it is written as a perilous place—since it divides between Jews and Arabs. Tel Aviv is also the place where one can imagine a great future or see a concealed history. It is a total urban experience, encapsulating the individual.